Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan pada Koperasi Anugerah Mega Mandiri Abadi - Renny Afrianti; Natal Indra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study analyzed how work environment and compensation can affect job satisfaction at The Head Office of Koperasi Anugrah Mega Mandiri. The method used in this research is quantitative descriptive method with data collection techniques using non-probability sampling with the population of 232 employees and obtained 70 respondents as the sample using Syolin formula. The data collection using a questionnaire in Liker scale unit and process the data using SPSS 26 for instrument test, multiple linear regression analysis, and hypothesis test.The result shows that the variables (X1, X2) have influence the job satisfaction of the employees (Y) proven by the T test for the work environment as the variable that effect the job satisfaction, where the value of thitung (6,655) > ttabel (1,996) with a significance value 0,000 (sig < 0,05), and the compensation influence the job satisfaction, where the value of thitung (4,912) > ttabel (1,996) with a significance value 0,000 (sig < 0,05). The variables (X1, X2) simultaneously influence the job satisfaction of the employees (Y) at Koperasi Anugrah Mega Mandiri proven by the F test that shows the Fhitung (51,451) > Ftabel (3,13) with a significance value 0,000 (sig < 0,05).